(untitled) (Revista Científica UCOM Scientia, 2025)
Type 2 diabetes mellitus is a growing public health concern worldwide and in Latin America, with significant effects on quality of life and health system performance. Early identification of risk factors in specific communities enables targeted preventive strategies and strengthens primary health care. This study aimed to assess the risk of type 2 diabetes mellitus in the Villa Guillermina community of Pedro Juan Caballero, Paraguay, in 2023. An observational, descriptive, cross-sectional study was conducted using the FINDRISC questionnaire, validated in Spanish by the International Diabetes Federation and the World Health Organization. The survey was carried out in November 2023 during a community diabetes prevention event with a sample of 89 individuals of both sexes and various ages. Patients with a prior diagnosis of diabetes mellitus and pregnant women were excluded. Most participants were male (69%) and younger than 45 years (77%). Sixty-five percent had a BMI <25 kg/m² and 69% had a waist circumference <94 cm. Physical activity was reported by 66% of respondents, 82% consumed fruit daily, 91% were not on antihypertensive drugs, and only 11% had elevated glucose levels. Eighty percent reported no family history of diabetes. The overall risk level was low in 92% of the population, moderate in 3%, and very high in 5%. These findings indicate a generally low risk of developing type 2 diabetes mellitus in this community but highlight the importance of continuing preventive and educational actions to sustain healthy lifestyles.